2021
DOI: 10.3390/antibiotics10091108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Staphylococcus aureus Associated with Meat and Meat Products in African Countries: A Review

Abstract: Antimicrobial resistance has been increasing globally, which negatively affects food safety, veterinary, and human medicine. Ineffective antibiotics may cause treatment failure, which results in prolonged hospitalisation, increased mortality, and consequently, increased health care costs. Staphylococcus aureus causes a diverse range of infections including septicaemia and endocarditis. However, in food, it mainly causes food poisoning by the production of enterotoxins. With the discovery of methicillin-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 113 publications
(173 reference statements)
1
24
0
Order By: Relevance
“…Other studies showed that 29.4% of meat samples carried S. aureus . Additionally, other researchers have reported cross-contamination of meat samples through contact areas in butcher’s shops by S. aureus [ 29 ]. In a comparable study, E. coli strains have been found at 43.75% and 29.17% in minced meat and contact surfaces of butcher’s shops, respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that 29.4% of meat samples carried S. aureus . Additionally, other researchers have reported cross-contamination of meat samples through contact areas in butcher’s shops by S. aureus [ 29 ]. In a comparable study, E. coli strains have been found at 43.75% and 29.17% in minced meat and contact surfaces of butcher’s shops, respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin-resistant S. aureus from food of animal origin has been widely reported in several studies in different countries [27]. For example, in the Netherlands, 267 MRSA isolates (11.9%) were found from 2217 samples of raw meat obtained from market traders: Turkey (35.3%), chicken (16.0%), veal (15.2%), pork (10.7%), beef (10.6%), and lamb and mutton (6.2%); most of these MRSA isolates were included in LA-MRSA CC398 [10]. A recent study conducted in Brazil found MRSA isolates in samples of pork (37.5%), fish meat (30%), chicken (23.3%), and beef (23.3%) [28].…”
Section: Methicillin-resistant S Aureus In the Meat Of Animal Originmentioning
confidence: 99%
“…One of the most widely identified types of LA-MRSA in pig farming is clonal complex 398 (CC398), which has been widespread in pig farms worldwide [5,6]. Then, LA-MRSA began to be identified in other livestock, including cattle [7], poultry [8], and meats, including beef, lamb, poultry, and pork [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All AMU practices (judicious and non-judicious) in animals for both therapeutic and non-therapeutic purposes may propagate the shedding of substantial amounts of AMR microorganisms [ 2 , 3 , 4 ]. Currently available evidence on the impact of AMU in food animals on AMR in human pathogens is debatable [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Despite the controversies around the impacts of AMU in animals on public health, judicious practices among producers are widely used by all sectors within the animal agriculture food production system to prolong the efficacy of current antimicrobial agents [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%